Skrining Fitokimia & Aktivitas Antibakteri Ekstrak Bunga Telang (Clitoria ternatea L.) terhadap Bakteri Staphylococcus epidermidis - Sesilia, Riana; Priamsari, Margareta Retno; Akbar, Nanda Dwi (Jurnal Farmasi & Sains Indonesia, 2024)
Telang flowers contain secondary metabolite compounds that have benefits as antibacterial or antiseptic compounds including flavonoids, tannins, alkaloids and saponins. This research was an experimental research. Telang flower extract was obtained using 70% ethanol solvent by remaceration method then it tested like phytochemical content. Antibacterial activity testing with variaty concentrations media MHA (Mueller Hinton Agar) 15, 30, 45, 60, and 75% against Staphylococcus epidermidis. The positive control was Klindamycin. The obtained data were analyzed by Statistical Package for the Social Sciences (SPSS). The results shown that telang flower extract with concentrations 15, 30, 45, 60 and 75% had an average inhibition zone activity against Staphylococcus epidermidis were respectively 4.45 (15%); 4.63 (30%); 4.35 (45%); 5.47 (65%); and 7.02 mm (75%). The SPSS results show that the p value is <0.05 at the 95% confidence level, which indicates that there is a significant difference in antibacterial activity between butterfly pea flower extracts between concentrations of 15, 30, 45, 60, and 75%. Post hoc tests using LSD showed that there was a difference in antibacterial activity between concentrations of 75% and concentrations of 15, 30, 45, and 60%, but there was no difference in antibacterial activity between concentrations of 15, 30, 45, and 60%.Minimal inhibitor concentration of telang flower extract was obtained at 15%